Oil & gas produced water retention ponds as potential passive treatment for radium removal and beneficial reuse. Issue 3 (19th March 2021) - McDevitt, Bonnie; McLaughlin, Molly C.; Blotevogel, Jens; Borch, Thomas; Warner, Nathaniel R.
Abstract : Oil and gas extraction generates large volumes of produced water (PW) in regions that are water-stressed. PW can be passively treated in retention ponds prior to beneficial use. Oxic conditions lead to sequestration and lower bioavailability of Ra. Abstract : Oil and gas (O&G) extraction generates large volumes of produced water (PW) in regions that are often water-stressed. In Wyoming, generators are permitted under the National Pollutant Discharge Elimination System (NPDES) program to discharge O&G PW for beneficial use. In one Wyoming study region, downstream of the NPDES facilities exist naturally occurring wetlands referred to herein as produced water retention ponds (PWRPs). Previously, it was found that dissolved radium (Ra) and organic contaminants are removed within 30 km of the discharges and higher-resolution sampling was required to understand contaminant attenuation mechanisms. In this study, we sampled three NPDES discharge facilities, five PWRPs, and a reference background wetland not impacted by O&G PW disposal. Water samples, grab sediments, sediment cores and vegetation were collected. No inorganic PW constituents were abated through the PWRP series but Ra was shown to accumulate within PWRP grab sediments, upwards of 2721 Bq kg −1, compared to downstream sites. Ra mineral association with depth in the sediment profile is likely controlled by the S cycle under varying microbial communities and redox conditions. Under anoxic conditions, common in wetlands, Ra was available as an exchangeable ion, similar to Ca, Ba and Sr, and S was mostly water-soluble. 226 Ra concentration ratios in vegetation samples, normalizing vegetation Ra to sediment Ra, indicated that ratios were highest in sediments containing less exchangeable 226 Ra. Sequential leaching data paired with redox potentials suggest that oxic conditions are necessary to contain Ra in recalcitrant sediment minerals and prevent mobility and bioavailability.